Smoking and schizophrenia - Šagud, Marina (Array, 2009)
Smoking prevalence for schizophrenic patients is higher than this for general population. More than 60% of schizophrenic patients are current smokers, which contributes to excessive mortality in these patients. The reasons for high frequency of both smoking prevalence and heavy smoking in schizophrenic patients is thought to be at least partially related to enhancement of brain dopaminergic activity, which, in turn, results in behavioral reinforcement due to stimulant effects. Smoking stimulates dopaminergic activity in the brain by inducing its release and inhibiting its degradation. There is also evidence that cigarette smoking can reduce deficits relative to dopamine hypofunction in prefrontal cortex. Schizophrenic patients who smoke may require higher dosages of antipsychotics than nonsmokers